PERSPEKTIF FAMILY IMMUNITY DALAM PENCEGAHAN COVID-19 : A LITERATURE REVIEW - Zakaria, Achmad; Khusniyah, Zulfa (Jurnal EDUNursing, 2020)
Abstract               The social order cannot guarantee that the community will adapt well to the New Normal order, then it is certain that the transmission of Covid-19 transmission and the addition of cases will continue. In the context of preventing Covid-19, the family can be the main defense in warding off the transmission of transmission and the negative impacts caused by the Covid-19 pandemic. The negative impact of the Covid-19 pandemic has led to social transformations that can destabilize the existence of individuals and families so that they become vulnerable or even potentially do not have Family Immunity. Family immunity to COVID-19 can be described as a form of family strength-oriented approach in involving the family system as a whole through active processes in the form of coping, adaptation and positive behavior patterns so that they have the endurance in responding to stressors and crises caused by COVID. -19. Keywords : Family Immunity, New normal, Covid-19.